ROLE OF GREEN ENVIRONMENT IN CLIMATE CHANGE DIGITAL MARKETING STRATEGIES AND THEIR IMPACT ON CONSUMER BEHAVIOR (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Because of the growing sense of urgency around the issue of climate change, there has been an increased emphasis placed on environmentally responsible practices across a variety of industries, including digital marketing. This study investigates the role that green surroundings have in the formation of digital marketing strategies and the following influence that these tactics have on the behavior of consumers. The purpose of this study is to investigate the ways in which businesses are utilizing digital platforms to engage consumers who are environmentally concerned through the implementation of eco-friendly activities and sustainable messaging. The research identifies important initiatives, such as promoting environmentally friendly items, establishing green certifications, and making use of digital resources, in order to lessen the impact that humans have on the environment. As an additional point of interest, it investigates the impact that social media, content marketing, and influencer partnerships have in the development of a green brand identity. An analysis is conducted to determine the influence that these efforts have had on customer behavior, with a specific emphasis placed on the move toward environmentally conscious purchase decisions and brand loyalty. The purpose of this paper is to give insights into how digital marketing, when linked with environmental sustainability, may promote both brand success and beneficial contributions to climate change mitigation. These insights will be provided through the examination of case studies and consumer surveys.